Economic Value and Perception of Visitors Mangrove Bee Jay Bakau Resort (BJBR) Probolinggo, East Java - Muhammad Fajar Maulana (Faculty of Fisheries and Marine Science, Brawijaya University, 2021)
The concept economic value is based on availability paying (Willingness to pay) a person to consume goods and services produced by natural resource or the environment.The purpose this study was to analyze characteristics of mangrove attractions, characteristics of visitors, visitor perceptions of sapta charm, and estimate the economic value in BeeJay Bakau Resort Probolinggo. Descriptive research with data collection methods including interviews, observation, documentation and questionnaires. The sampling method uses accidental sampling technique and determination of the number samples using the linear time function formula. For the dependent variable that is number of requests for visits to mangrove tourism and independent variables namely travel costs, distance traveled, education level, income level, age, and working day (HOK). The result of the analysis shows that the visitor's perception of sapta charm in the mangrove tourist attraction which dominates is the friendly aspect of 34.25% while the economic value is IDR 638,287,712,178/year and the total value of the receipts is IDR 4,200,000,000. Suggestions in order increase the potential tourism there because the economic value is higher than value of acceptance as well as research on the aspect of charm so that the development of tourist objects is in line with what visitors want.